Millets - Rediscover Ancient Grains 2024
DOI: 10.5772/intechopen.110548
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Properties, Nutraceutical Potential of Different Millets, and Their Value-Added Food Products

Abstract: Millets are one of the oldest food grains known to mankind. They are considered underutilized crops and can sustain in harsh environments with limited water resources where other crops grow or yield poorly. Millets are very adaptable: they thrive in dry regions, on clay soils, in wet lowlands, or alluvial lands. Their root systems are powerful, able to descend very quickly to a great depth of soil to extract water and minerals, and thus have high adaptability to climate change, especially drought. Millets have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The high carbohydrate content (81.0% ± 0.7) of the composite flour (Table II) was due to the high inclusion of carbohydrate-rich ingredients in the formulation, that is, 44% maize, 26% millet, 18% amaranth grains and 12% sugar. Maize, millet and amaranth grains contain about 73% [38], 65%-75% [39] and 65% [40] carbohydrates, respectively. Similarly, a high carbohydrate content (88.8%) was reported for cowpea-maize composite flour [41].…”
Section: Nutritional Composition Of the Composite Flourmentioning
confidence: 99%
See 1 more Smart Citation
“…The high carbohydrate content (81.0% ± 0.7) of the composite flour (Table II) was due to the high inclusion of carbohydrate-rich ingredients in the formulation, that is, 44% maize, 26% millet, 18% amaranth grains and 12% sugar. Maize, millet and amaranth grains contain about 73% [38], 65%-75% [39] and 65% [40] carbohydrates, respectively. Similarly, a high carbohydrate content (88.8%) was reported for cowpea-maize composite flour [41].…”
Section: Nutritional Composition Of the Composite Flourmentioning
confidence: 99%
“…The low crude protein content (8.2% ± 0.1) of the composite flour (Table II) was due to the low protein content of the ingredients in the formulation that is; 18% amaranth grain, 44% maize and 26% millet with approximately 14% [40], 9% [38] and 7%-12% [39] protein, respectively. The protein content of the composite flour in this study was lower than what Gemede [43] reported for flour blends of maize, peas and anchote, which were 15%-21%.…”
Section: Nutritional Composition Of the Composite Flourmentioning
confidence: 99%